2004
DOI: 10.1086/426460
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the X-Linked Cyclin-Dependent Kinase–Like 5 (CDKL5/STK9) Gene Are Associated with Severe Neurodevelopmental Retardation

Abstract: Recently, we showed that truncation of the X-linked cyclin-dependent kinase-like 5 (CDKL5/STK9) gene caused mental retardation and severe neurological symptoms in two female patients. Here, we report that de novo missense mutations in CDKL5 are associated with a severe phenotype of early-onset infantile spasms and clinical features that overlap those of other neurodevelopmental disorders, such as Rett syndrome and Angelman syndrome. The mutations are located within the protein kinase domain and affect highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
231
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(244 citation statements)
references
References 27 publications
(33 reference statements)
4
231
0
4
Order By: Relevance
“…67 -70 Moreover, recent data showed that mutations in the cyclin-dependent protein kinase-like 5 (CDKL5/STK9) are responsible for neurodevelopmental disorder with clinical features that are reminiscent of Rett's syndrome. 71,72 Given the clinical overlap resulting from mutation in MECP2 and CDKL5 genes, their involvement in a common genetic and pathogenic pathways has been suspected and further studies showed that spatio-temporal expression of Cdkl5 overlaps with that of Mecp2 and that Mecp2 and Cdkl5 interact in vivo and in vitro. 73 MeCP2 was first identified as a member of the methylCpG-binding domain (MBD) protein family.…”
Section: Genetics and Pathophysiology Of Mr J Chelly Et Almentioning
confidence: 99%
“…67 -70 Moreover, recent data showed that mutations in the cyclin-dependent protein kinase-like 5 (CDKL5/STK9) are responsible for neurodevelopmental disorder with clinical features that are reminiscent of Rett's syndrome. 71,72 Given the clinical overlap resulting from mutation in MECP2 and CDKL5 genes, their involvement in a common genetic and pathogenic pathways has been suspected and further studies showed that spatio-temporal expression of Cdkl5 overlaps with that of Mecp2 and that Mecp2 and Cdkl5 interact in vivo and in vitro. 73 MeCP2 was first identified as a member of the methylCpG-binding domain (MBD) protein family.…”
Section: Genetics and Pathophysiology Of Mr J Chelly Et Almentioning
confidence: 99%
“…A small handful of mutations in CDKL5 has been identified recently in patients with an early seizure phenotype of atypical RTT (Archer et al 2006a, b;Evans et al 2005a;Mari et al 2005;Scala et al 2005;Tao et al 2004;Weaving et al 2004). To date, 15 different CDKL5 mutations have been identified in 15 atypical RTT patients with early onset seizure disorder.…”
Section: Cdkl5 Mutation Analysismentioning
confidence: 99%
“…Several reports have identified large gene deletions in RTT patients that escaped detection by PCR-based screening strategies (Laccone et al 2004;Schollen et al 2003). Others have identified mutations in a novel MeCP2 isoform and in CDKL5 (Archer et al 2006a, b;Evans et al 2005a;Kriaucionis et al 2004;Mari et al 2005;Scala et al 2005;Tao et al 2004;Weaving et al 2004). This study reports the results of the mutation analysis of MECP2 and CDKL5 in 121 unrelated Chinese patients with classic or atypical RTT, conducted to obtain a genotypic representation of the mutational spectrum in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Point mutations or genomic deletions in MECP2 have been identified in greater than 90% of patients with typical Rett syndrome. 1,2 In 30-50% of patients with atypical Rett syndrome, 3 negative for alterations in MECP2, intragenic changes in CDKL5 [4][5][6][7][8] or in FOXG1 [9][10][11] have been reported.…”
Section: Introductionmentioning
confidence: 99%